Efektivitas Daun dan Buah Pinus merkusii sebagai Bahan Pengawet Anti Jamur Auricularia auricula-judae: Effectiveness of Pinus Merkusii Leaves and Fruits as Antifungal Preservative Auricularia auricula-judae - Arista, Andi Sindy Wahyuni; Taskirawati, Ira; Agussalim, A (Forestry Faculty of Hasanuddin University, 2022)
Chemicals such as chromium, arsenic, and kreosot which are carcinogenic and toxic which are harmful to health and the environment are generally used in wood preservatives. Thus, natural preservatives from plant extracts need to be developed to replace these synthetic preservatives. Pine leaves and nuts are known to contain phenolic compounds in which these compounds are known to inhibit the cycle and development of fungi. The purpose of this study was to analyze the efficacy of powdered leaves and pine nuts (P. merkusii) against rotting fungus Auricularia auricula-judae. This research method uses testing for water content, the extract is made by means of fruit and leaf powder each as much as 150 g is put into a beaker containing 900 ml of methanol solution with a ratio of 1:6 powder and methanol solvent, soaked for ± 3x24 hours, filtered until the filtrate is clear, and evaporated with a rotary vacuum evaporator. After that, the extract was evaporated again in a water bath at 45°C for 48 hours to dry. The yield is then weighed and calculated. Preparation of leaf and fruit powder concentrations. At concentrations of 25 ppm, 50 ppm, 75 ppm and 100 ppm. The efficacy test of P. merkusii leaf and fruit powder against rot fungi consisted of five treatments, with 45 petri dishes as samples and each treatment consisted of five replications. The results of the research that had been carried out obtained an AFA value of 100% indicating that the powdered leaves and fruit of P. merkusii had antifungal activity which was included in the very strong classification. At a concentration of 25% powdered leaves and pine nuts can already inhibit the growth of the fungus Auricularia auricula-judae.